Aquifer Vulnerability Assessment by DRASTIC and SI methods: The case study of Guelma Plain, Northeast Algeria - Baazi, Houria (Engineering, Technology & Applied Science Research, 2023)
Guelma plain, located in northern Algeria, contains an alluvial nappe that provides economic opportunities such as industrial and agricultural employment. In Guelma, the pressure of anthropogenic origin is combined with unfavorable climatological conditions that expose it to environmental and social risks. The current study aims to assess the level of groundwater vulnerability to pollution using two methods, DRASTIC and SI. These are coupled with the Arc Gis software in order to carry out the mapping. From south to north, several levels of vulnerability have been identified, from low to high. The result comparison allows us to conclude that the SI method is the most appropriate for assessing the vulnerability to pollution of the study region’s wetlands. The result of this study can be used as a decision-support tool for the management and protection of the quality of water resources in the Guelma plain.